2016
DOI: 10.1002/anie.201607375
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymers: Catalysts for Photocatalytic Hydrogen Evolution

Abstract: Conjugated polymers, comprising fully π-conjugated systems, present a new generation of heterogeneous photocatalysts for solar-energy utilization. They have three key features, namely robustness, nontoxicity, and visible-light activity, for photocatalytic processes, thus making them appealing candidates for scale-up. Presented in this Minireview, is a brief summary on the recent development of various promising polymer photocatalysts for hydrogen evolution from aqueous solutions, including linear polymers, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
440
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(446 citation statements)
references
References 145 publications
1
440
0
5
Order By: Relevance
“…To the best of our knowledge, the photocatalytic activity of CTF-1-100W shows much superior quantum efficiency for water oxidation to any reported carbon based or carbon-nitride based polymer photocatalyst, according to the recently published reviews. 21,56 As shown in Table S1 (ESI †), the new polymer photocatalyst synthesised by our approach almost presents both the highest H 2 and O 2 evolution rates under visible light irradiation, 22,45,[57][58][59][60][61][62] which is attributed to the well-controlled crystallisation by tuning the microwave power and the avoidance of carbonisation.…”
mentioning
confidence: 81%
“…To the best of our knowledge, the photocatalytic activity of CTF-1-100W shows much superior quantum efficiency for water oxidation to any reported carbon based or carbon-nitride based polymer photocatalyst, according to the recently published reviews. 21,56 As shown in Table S1 (ESI †), the new polymer photocatalyst synthesised by our approach almost presents both the highest H 2 and O 2 evolution rates under visible light irradiation, 22,45,[57][58][59][60][61][62] which is attributed to the well-controlled crystallisation by tuning the microwave power and the avoidance of carbonisation.…”
mentioning
confidence: 81%
“…79 First, the research on metal-free photocatalysts for water splitting has gained momentum with the discovery in 2009 that polymeric carbon nitride can act as a photocatalyst for hydrogen and oxygen generation from water. 135 In the following years more than one thousand papers have appeared on the usage of polymeric carbon nitride for photocatalytic applications.…”
Section: Cmps For Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…77,78 Furthermore, conjugated microporous polymers have come into focus of catalysis research, especially for photocatalysis. 79 This point will also be discussed in more detail later. Excellent and comprehensive reviews on the use of microporous polymers for catalytic applications were recently published by Rose 40 and Zhang and Ying.…”
mentioning
confidence: 93%
“…Organic semiconductor (OS)-containing photocatalysts have emerged as a promising alternative to traditional metalcontaining photocatalysts due to their highly tunable electronical properties via flexible structural design. Recent research activities have demonstrated a vast number of structural design methods of small molecular 8,10,[16][17][18][19][20] or macromolecular [21][22][23][24][25][26][27][28][29][30] OS systems as efficient photocatalysts for visible light-promoted photoredox reactions. Nevertheless, most developed OS photocatalysts, similar to traditional transition metal complexes, [31][32][33][34][35][36][37][38] are single photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%